Effectiveness study of Artemisia herba-alba and Borage officinalis leaf extract against bacteria Staphylococcus aureus - Raghad A. AL.Askary; Haider R. Malih (University of Thi-Qar Journal of Science, 2021)
The inhibitory efficacy of aqueous extract of Artemisia herba-alba and Borago officinalis leaves was evaluated a type of bacterium that posits a cram stain, including the isolated Staphylococcus bride the results showed efficacy against microbial for both extracts The bacteria are under study. Some of the active compounds have been detected in the leaves of Artemisia herba-alba and Borago officinalis These leaves were found to contain (tannins, alkaloids, resins, soaps, phenols, flavonoids and Glycoside). Also, the sensitivity of this isolation was studied for some antibiotics, and most of them were resistant to Ceftriaxone, Amikacin, Imipenem, Ciprofloxacin, with a rate of 100%. The results show Synergism efficacy when mixing the antibiotic Ceftriaxone, Amikacin, Imipenem, Ciprofloxacin with each of the aqueous extracts of the blocks Artemisia herba-alba and Borago officinalis on a different bacterium under study.